Effect of Seed Size and Temperature Treatments on Germination of Various Seed Sources of Pinus wallichiana and Pinus roxburghii from Garhwal Mmalaya - Ghildiyal, S. K.; Sharma, C. M. (Indian Forester, 2005)
The present study was undertaken to find out the effect of Hydrogen peroxide on germination of various provenances of Pinus wallichiana and Pinus roxburghii, which had a significant affect on rate and average germination percentage. It has been observed that H2O2 treatment has reduced the germination period of these species appreciably down to 8 days and 10 days respectively. Therefore, seeds of these commercially important tree species should be pre- treated particularly with H2O2 1 % v/v for 24 hours to obtain optimum germination. The large sized seeds in Pinus wallichiana (mean germination percentage, 54.66%) and medium sized seeds in Pinus roxburghii (mean germination percentage, 93.33%) have been recorded favourable for getting increased seed germination under laboratory conditions.